Yield and quality performances of four tea test clones (Journal of the Bangladesh Agricultural University, 2012)
An experiment was carried out during 19942007 to investigate the yield and quality performances of four vegetatively propagated test clones of tea viz. SH/D/11/13, SH/D/11/333, B/HB/2/3 and B/HB/6/4. Two clones, BT1 and TV23, were used as check for quality and yield, respectively. Cuttings of the test clones were collected from the selected bushes of Shumshernugger Tea Estate and hybrid lines of Bangladesh Tea Research Institute (BTRI) and were raised at BTRI nursery. Then the saplings were managed for long term yield and quality trial following randomized complete block design with 5 replications. The green leaf was harvested at weekly interval during the plucking season starting from mid March to mid December throughout the experimental period. The overall cup quality of the test clones was assessed by conventional organoleptic test. At the immature stage (2nd5th year after plantation), all test clones showed similar yield trend as that of check BT1. At the mature stage (6th13th year), the test clones SH/D/11/333 and B/HB/6/4 gave the significantly higher average yield (3095 and 3342 kg ha1 made tea, respectively) compared to the check BT1 (3042 kg ha1 made tea). The cup quality of all the test clones and BT1 was found to be Above Average while the cup quality of TV23 was Average. Considering the overall performances, the test clones SH/D/11/333 and B/HB/6/4 have been released as BT13 and BT14, respectively for commercial plantation in the tea estates. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12036 J. Bangladesh Agril. Univ. 10(1): 3338, 2012